Muscle Tear and Hematoma of the Vast Medial in Septuagenarian (Revista de Medicina Clinica, 2022)
Clinical Snapshot on Muscle Tear and Hematoma of the Vast Medial in Septuagenarian presented in Volume 6 Issue 3 of the Revista de Medicina Clínica
Keywords: Muscular tear; Hematoma; Vast Internal Muscle